2016
DOI: 10.1111/ppc.12162
|View full text |Cite
|
Sign up to set email alerts
|

Is Health Literacy Associated With Depressive Symptoms Among Korean Adults? Implications for Mental Health Nursing

Abstract: Health literacy may play an important role in preventing and treating depression. Future research is needed to determine if improving health literacy, through health promotion interventions, can enhance community-dwelling Korean adults' understanding of depressive symptoms and relevant treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
1
17
0
2
Order By: Relevance
“…Earlier studies reported that individuals with lower health literacy often hide their health problems from family, friends, and healthcare providers because of shame, thereby causing them to likely experience isolation and to perceive less available support (67). Moreover, another study indicated that health literacy can act as an asset and empowerment tool that helps individuals access education about mental health services and utilize existing mental health services (68). Accordingly, to decrease depression and boost social support among older hypertensive and diabetic patients, efforts should be made by health care providers and policymakers to improve the health literacy of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies reported that individuals with lower health literacy often hide their health problems from family, friends, and healthcare providers because of shame, thereby causing them to likely experience isolation and to perceive less available support (67). Moreover, another study indicated that health literacy can act as an asset and empowerment tool that helps individuals access education about mental health services and utilize existing mental health services (68). Accordingly, to decrease depression and boost social support among older hypertensive and diabetic patients, efforts should be made by health care providers and policymakers to improve the health literacy of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The MHL mean score, health literacy mean score, social support mean score, depression mean score, and mental health facility use score were all transformed using the natural logarithm function to interpret the results in approximate percentage changes rather than unit changes in the multiple regression analysis. to be associated with greater prevalence of mental illness symptoms, [43][44][45] and poor parental health literacy predicted negative mental well-being for their children. 46 Furthermore, populations with low health literacy are less likely to seek professional help for mental illness symptoms 44,47 and…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy is defined as the "degree to which individuals have the capacity to obtain, process, and understand basic health information and services needed to make appropriate health decisions" (21). Previous studies have demonstrated that poor literacy is associated with higher levels of depressive symptoms in populations of US smokers with low socioeconomic status, US adults with addictions, and Korean adults (22)(23)(24). Additionally, a study of patients with diabetes indicated that depression may reduce the positive effect of health literacy on self-management (25).…”
Section: Introductionmentioning
confidence: 99%